Pengaruh Disiplin Kerja, Motivasi Kerja, dan Lingkungan Kerja Pada Karyawan PT. Manaya Indonesia Tour Travel - Azizah Bayu Wulandari; Cindy Choridatul Muawanah; Khoirlun Nisa; Moch. Tegarl Pratama; Muhammad Wahyu Maulana (BADAN PENERBIT STIEPARI PRESS, 2023)
Human resources are a very important factor in an organization, because the quality of the organization itself is very dependent on the quality of human resources as employees and service providers in an organization. Good human resource management with the right strategy will provide progress for the company, especially in dealing with situations and conditions that are always changing and developing. This study aims to determine whether work motivation, work discipline and work environment have a significant effect on job satisfaction at PT. Manaya Indonesia Tour and Travel. The population in this study were all employees of PT. Manaya Indonesia Tour Travel. The sampling technique is saturated sampling, by taking the entire sample as much as 60 respondents. By using the associative method with multiple linear regression analysis techniques. The results of the study show that motivation, discipline and work environment simultaneousy have a significant effect on employee job satisfaction. Motivation partially has a significant effect on employee job satisfaction, while discipline and work environment have no significant effect. Preferably the leadership of PT. Manaya Indonesia Tour and Travel increases the work discipline of employees so that it will improve performance.